Two-dimensional electromagnetic scattering analysis based on the boundary element method - Hu, Qian; Liu, Chengmiao (Frontiers in Physics, 2024)
An effective formula for shape sensitivity analysis of electromagnetic scattering is presented in this paper. Firstly, based on the boundary element method, a new electromagnetic scattering formula is derived by combining the traditional electromagnetic scattering formula with the nonuniform rational B-spline curve, and the geometric model is represented by NURBS, which ensures the geometric accuracy, avoids the heavy grid division in the optimization process, and realizes the fast calculation of high-fidelity numerical solutions. Secondly, by deducing the sensitivity variables, the electromagnetic scattering equation of shape optimization is obtained, which can provide reliable data reference for shape optimization. Finally, the accuracy and effectiveness of IGABEM method are verified by two calculation columns.